(Freedom from dependency among students of the Department of Psychological Counseling and Educational Guidance) (build and apply) (Journal of the College of Basic Education, 2022)
Personal effectiveness is one of the important qualities in a normal personality for the individual’s sense of responsibility in all its fields, whether it is towards the family or the institution in which he works, or towards his friends, neighbors and other people with whom he mixes, or towards the general community, even if each individual feels responsible towards him other than people and towards the work that he does, for the progress of society and the advancement of all its members and the goodness of all of them.Search objective:1- Building a scale of personal effectiveness among students of the Department of Psychological Counseling and Educational Guidance.2- Identifying the personal effectiveness of the students of the Department of Psychological Counseling and Educational Guidance. The researcher built a scale of freedom from dependence, which consists of (32) items, in a five-graded declarative style, and extracted the psychometric properties of honesty (discriminative power, internal homogeneity and stability by re-test method, the (Alpha-Cronbach) equation and the statistical indicators of the scale, and verifying the second objective using T-test for one sample.The research reached the following results:To complement the current research, the researcher presented a number of recommendations and suggestions.